A GIS-based walkability index for the City of Cape Town - Van Heerden, Schalk Willem (School of Architecture, Planning and Geomatics, 2018)
Walking is a widely accessible mode of transportation, yet our urban environments are automobile dependent. Automobile dependence, in turn, led to a rise in the level of inactivity amongst urban residents. Studies investigating the relationship between urban form and human health created walkability indices measuring urban environmental features contributing to the walkability of an area. However, walkability has only recently become the subject of research within urban planning. Within a South African context limited research is available on walkability and to date, there is no metropolitan-wide walkability index for any South African metropolitan. The research presented in this dissertation addresses the gap in South African walkability studies through the composition of a walkability index for Cape Town. From previous studies, the research identifies three main measures of walkability. These measures and a fourth Cape Town specific measure of walkable areas around informal and formal destinations are quantified and mapped using GIS research methods and techniques. The GIS results are validated against field validations points depicting streetscapes within enumeration areas. Based on the results and the validation thereof the study suggests possible applications of the walkability index for non-motorised transport planning in Cape Town.